2008
DOI: 10.1002/bit.21992
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of human immune effector T cells containing iron‐oxide nanoparticles

Abstract: Preparation of human immune T cells containing iron-oxide nanoparticles was carried out for the development of magnetically mediated immunotherapy. Peripheral blood lymphocytes (PBLs) after the incubation with magnetite nanoparticles were found to contain measurable ferric ions, which suggested the incorporation of magnetite nanoparticles. Transmission electron microscopic (TEM) study indicated that the incorporation of magnetite nanoparticles was mediated by endocytosis of PBLs. Furthermore, the effects of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
5
19
0
Order By: Relevance
“…Previous studies have shown endosomal SPION uptake into CTLs for the purpose of T-cell tracking through the body by magnetic resonance imaging (MRI) 33,35 and T-cell magnetically mediated immunothermotherapy for melanoma. 34 As seen in other studies, we observed endosomally located Feraspin R, and the uptake increases dose-dependently and on transfection-agent treatment (Figures 1 and 2). SQUID has advantages over other ironquantification methods, such as inductive coupled plasma atomic absorption spectroscopy and atomic absorption spectroscopy, 38 which likely overestimate iron levels by not distinguishing between nonparamagnetic and paramagnetic iron.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Previous studies have shown endosomal SPION uptake into CTLs for the purpose of T-cell tracking through the body by magnetic resonance imaging (MRI) 33,35 and T-cell magnetically mediated immunothermotherapy for melanoma. 34 As seen in other studies, we observed endosomally located Feraspin R, and the uptake increases dose-dependently and on transfection-agent treatment (Figures 1 and 2). SQUID has advantages over other ironquantification methods, such as inductive coupled plasma atomic absorption spectroscopy and atomic absorption spectroscopy, 38 which likely overestimate iron levels by not distinguishing between nonparamagnetic and paramagnetic iron.…”
Section: Discussionsupporting
confidence: 88%
“…SQUID has advantages over other ironquantification methods, such as inductive coupled plasma atomic absorption spectroscopy and atomic absorption spectroscopy, 38 which likely overestimate iron levels by not distinguishing between nonparamagnetic and paramagnetic iron. Iron concentrations are calculated indirectly in the colorimetric potassium thiocyanate method, 34 on the assumption that full oxidation or reduction of a dissolved sample occurs. A concentration of 53 pg/cell ( Figure 2B) was measured in our study poststarvation and on protamine sulfate treatment, a much higher value than that observed by Beer et al, 33 but our results matched those observed using Resovist analogues in other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations